Quantifying the impacts of invasive N2-fixing plants on relative sediment loads and nutrient concentrations in mountain streams of the Cape Floristic Region, South Africa - Wiener, Kenwinn Dane (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScConEcol)--Stellenbosch University, 2018.